CORRELATION OF GALL BLADDER WALL THICKNESS WITH SERUM PLATELETS COUNT AND HEMATOCRIT LEVELS IN DENGUE NSI POSITIVE PATIENTS - Saneela Mumtaz; Hooria Asif; Ayesha Nayab; Ayesha Qazi; Shahid Hussain (Journal of Ayub Medical College Abbottabad, 2025)
Background: Dengue fever, a mosquito-borne viral infection holds pathophysiology in form of the alteration of hematological parameters, particularly platelet count and hematocrit levels, which are indicators of disease severity. Among the radiological workup, gallbladder wall thickening is a notable ultrasonographic finding in dengue patients. Objective was to determine the correlation of gall bladder wall thickness with serum platelets count and hematocrit in dengue NSI positive patients. Methods: A total of 250 enrolled patients underwent a clinical assessment that included measuring gallbladder wall thickness via ultrasonography by trained radiologists, determining serum platelet count using standard hematology analyzers, and assessing hematocrit levels with standard laboratory techniques. These measurements were taken at consistent intervals, such as on admission and on days 3 and 5. An abdominal ultrasound was conducted by a single physician using portable bedside equipment, and all other clinical and laboratory data were obtained from the patients’ electronic records. Results: The mean age of the patients was 49.52±8.50 years. Gallbladder wall thickness was less than 3 mm in 50.9%, between 4-6 mm in 46.4%, and 7 mm or more in 2.7%. A significant inverse correlation was found between gallbladder wall thickness and platelet count (ρ = -0.861, p = 0.000) and a strong positive correlation with hematocrit levels (ρ = 0.873, p = 0.000). Conclusion: The present study concluded that evaluation of gallbladder wall thickness is an important step when performed in conjugation with serum platelets count and hematocrit in dengue fever to predict the disease severity and thus aids in the management and improving the outcome in dengue prone areas.